Computed tomography characteristics of fibrosarcoma — a histological subtype of feline injection-site sarcoma. Issue 6 (June 2013) - Travetti, Olga; di Giancamillo, Mauro; Stefanello, Damiano; Ferrari, Roberta; Giudice, Chiara; Grieco, Valeria; Saunders, Jimmy H
Feline injection-site sarcoma (FISS) may be a consequence of subcutaneous injection. In the present study, the medical records and the computed tomography (CT) features of 22 cats with a FISS, histopathological subtype fibrosarcoma, were used. The majority of the fibrosarcomas (45%) were located in the interscapular region. All fibrosarcomas, except one with mild enhancement, showed strong contrast uptake, characterised as ring (42%), heterogeneous (36%), homogeneous (9%), heterogeneous/ring (6.5%) or mixed heterogeneous/homogeneous enhancement (6.5%). The longest axis of the mass was in a cranio-caudal (68%) or dorso-ventral (32%) direction. The median volume calculated on CT was 7.57 cm 3 . Common features were a marked local invasiveness of the musculature and heterogeneity of the tissue in the periphery of the neoplasia. When the fibrosarcoma was interscapular, performing an additional post-contrast scan with the forelimbs positioned caudally along the body, in addition to the standard protocol with the forelimbs extended cranially, allowed better evaluation of the actual relationship between the tumour and the surrounding tissues. The mean number of muscles involved with the tumour was 2.09 with extended and 1.95 with flexed forelimbs. When a lower number of structures was considered infiltrated through the double positioning, a less invasive surgical approach to underlying muscles and scapula was performed.